User satisfaction of the grade 7 to 4th year high school students of the School Library of Philippine National School for the Blind - Vizcarra, Jamie Anne T.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2014)
School libraries contribute in developing the minds of children by complementing the curriculum of the school and instilling in children the love for reading. People with disabilities are one of the undeserved groups in the library. They also have the right to access needed information. A library should serve the whole school population. It should satisfy its users and encourage non-users to utilize what the library has to offer.
The researcher aimed to find the user satisfaction of the grade 7 to 4th year high school students and the teachers of the Philippine National School for the Blind (PNSB). Also, the researcher wants to know the reasons why the students and the teachers use or not use the school library. This study was done to improve the school library of PNSB.
A total of 32 students were interviewed and 10 teachers answered the questionnaires. The results showed that generally, the respondents are satisfied with the collection, equipment and services, and facilities of the school library. Also, the top 3 activities done by the students in the library are to read books, to borrow books and to do their assignments and the most used or borrowed materials in the library are story books. With the teachers, the top activity for them is using the library as part of their activity for their students. The top 3 reasons of the students' non-usage of the school library are uncomfortable tables and chairs, they have their own sources, and they are not aware what the school library has. The use of school computers after class was also asked from the students. The results showed that majority of the students do not use the school computers after class due to limited time.
The researcher recommended that the library should improve their collection, equipment and facilities, and services in order to up the quality of education that the students can have. Also, a need for concrete policies and systems is apparent. Future researchers should follow-up this study and encompass the opinions of the school population.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Philippine National School for the Blind -- students; Libraries -- User satisfaction; Libraries and people with visual disabilities -- Philippines -- Quezon City